Utilization of the Pixtoon Application in Learning for Prospective Elementary School Teachers: A Descriptive Study on Digital Comic Creation - Mila Handiyani; Sintya Widhiacarni Atmanastusti; Seflianti (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2026)
Learning in pre-service elementary teacher education requires the use of instructional media that can support accurate and engaging concept delivery. One alternative instructional medium that can be utilized is digital comics based on applications. This study aims to describe the use of the Pixton application in pre-service elementary teacher education through digital comic creation activities. The study employed a qualitative descriptive approach involving 48 third-semester students of the Elementary School Teacher Education program. Data were collected through classroom observation, digital comic creation assignments, and analysis of students’ work. The findings indicate that the use of the Pixton application provided meaningful learning experiences for students and encouraged the development of creative and contextual visual-based instructional media. Students also demonstrated positive responses toward the use of digital comics as a varied alternative instructional medium. These findings suggest that the Pixton application has the potential to be utilized in pre-service elementary teacher education to equip students with the ability to design engaging and meaningful instructional media.